Effects of aerodynamic interference on the iced straddling hangers of suspension bridges by wind tunnel tests. Issue 184 (January 2019) - Guo, Pan; Li, Shengli; Wang, Dongwei
Abstract: The wind-induced vibration of suspension bridge hangers may be ascribed to hanger icing. The aerodynamic characteristics of the iced straddling hangers of suspension bridges under various working conditions are analyzed in this paper via wind tunnel experiments. The analysis results show that the aerodynamic characteristics of leeward hangers are greatly influenced by the varying thicknesses of B- and D-shaped ice and suggest that lift force must be considered in the static analysis of suspension bridges. The hanger spacing of A × B = 8D × 4D, where the aerodynamic characteristics of leeward hangers with both B- and D-shaped ice are stable, can be used as reference for designers. The change in the aerodynamic coefficients of leeward hangers must also be considered when analyzing the stability of the straddling hangers of suspension bridges because iced hangers have different relative positions and the Strouhal number of leeward hangers rapidly fluctuate when the relative angle ( β ) is 4° . The shielding effect of windward hangers on leeward hangers with B- and D-shaped ice is most visible at a wind attack angle of −24°, and the drag coefficients of D-shaped iced hangers are obviously less than those of B-shaped iced hangers. The results of static analysis of suspension bridges are produce on non-conservative side results when hanger icing is disregarded. The findings of this study work can be used as references in the structural design and wind-resistance designs of suspension bridges with straddling hangers. Highlights: Aerodynamic characteristics of the iced straddling hangers of suspension bridges are analyzed via wind tunnel experiments. The aerodynamic characteristics of leeward hangers are greatly influenced by iced thicknesses. Lift force must be considered in the static analysis of suspension bridges. Static analysis results of suspension bridges are produce on non-conservative side results when hanger icing is disregarded.